THE INFLUENCE OF FINANCIAL RATIO ON FIRM VALUE IN CHEMICAL SUB SECTOR COMPANIES LISTED ON IDX (2020-2022)THE INFLUENCE OF FINANCIAL RATIO ON FIRM VALUE IN CHEMICAL SUB SECTOR COMPANIES LISTED ON IDX (2020-2022) - Herlina Nur Rahmasari; Nilmawati; Sri Dwi Ari Ambarwati (PT. Anagata Sembagi Education, 2024)
The aim of this study is to analyze the impact of return on equity, current assets, debt to assets ratio and total asset turnover ratio on the value of the company with a price to book value ratio measurement tool. The research was carried out on sub-sector companies Chemicals 2020-2023 which are listed on the Indonesian Stock Exchange. This research uses quantitative methods. The research population is a chemical sub-sector companies listed on the Indonesian Stock Exchange. Purposive sampling is the selection of samples using certain criteria of the research carried out. The analytical tool used in this study is double linear regression using SPSS 26. Debt to assets ratio has a significant and positive effect on the price to book value ratio, whereas current ratio and total assets turnover ratio have no significant effect on price to book value ratios.